2000
DOI: 10.1097/00004770-200012000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Increased Density of Gutta-Percha Using a Controlled Heat Instrument with Lateral Condensation

Abstract: The purpose of this study was to compare quantitatively the density of standard cold lateral gutta-percha condensation and warm lateral gutta-percha condensation using the System B heating instrument in a low-heat warm lateral condensation technique in an artificial root canal in vitro. Thirty-degree simulated root canals in 30 transparent acrylic blocks were instrumented using Gates-Glidden burs and Quantec (NT Company, Chattanooga, TN) rotary files. The canals were then obturated with gutta-percha using stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 10 publications
3
15
0
4
Order By: Relevance
“…Although warm filling techniques improve the compaction of gutta-percha into root canals, when compared with standard cold lateral compaction (Nelson et al 2000), it is still necessary to use a sealer to fill voids and gaps between the core material and canal walls. Without a sealer, both cold and warm filling techniques are associated with greater leakage (Schafer & Olthoff 2002, Wu et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Although warm filling techniques improve the compaction of gutta-percha into root canals, when compared with standard cold lateral compaction (Nelson et al 2000), it is still necessary to use a sealer to fill voids and gaps between the core material and canal walls. Without a sealer, both cold and warm filling techniques are associated with greater leakage (Schafer & Olthoff 2002, Wu et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Teeth obturated with cold lateral compaction (CLC) and different sealers exhibited leakage following minimal storage in saliva (5). Warm vertical compaction (WVC) can increase the GP mass density and homogeneity on previous CLC obturations (7,8). The WVC technique has shown greater ability to flow into canal irregularities (9 -11).…”
mentioning
confidence: 99%
“…Cold lateral condensation is one of the most widely used obturation techniques. Compared with thermoplastic obturation techniques, cold lateral condensation is reported to have possible disadvantages such as inhomogeneity, an increased risk of canal fracture, and poor adaptation to the canal walls [19]. Our study demonstrated a wide variance in the cold lateral condensation group during the pressure tests.…”
Section: Discussionmentioning
confidence: 65%